A Miniaturized Amperometric Hydrogen Sulfide Sensor Applicable for Bad Breath Monitoring - Gatty, Hithesh K. (Micromachines (Basel), 2018)
Bad breath or halitosis affects a majority of the population from time to time, causing personal discomfort and social embarrassment. Here, we report on a miniaturized, microelectromechanical systems (MEMS)-based, amperometric hydrogen sulfide (H(2)S) sensor that potentially allows bad breath quantification through a small handheld device. The sensor is designed to detect H(2)S gas in the order of parts-per-billion (ppb) and has a measured sensitivity of 0.65 nA/ppb with a response time of 21 s. The sensor was found to be selective to NO and NH(3) gases, which are normally present in the oral breath of adults. The ppb-level detection capability of the integrated sensor, combined with its relatively fast response and high sensitivity to H(2)S, makes the sensor potentially applicable for oral breath monitoring.